2020
DOI: 10.1111/jsap.13093
|View full text |Cite
|
Sign up to set email alerts
|

The natural history of canine occult Grade II medial patellar luxation: an observational study

Abstract: Objectives To determine the risk of lameness and the rate of subsequent medial patellar luxation surgery in dogs that present with occult Grade II medial patellar luxation. Materials and methods Retrospective owner survey and review of clinical records of adult dogs diagnosed with Grade II medial patellar luxation that were initially asymptomatic and managed non‐surgically that had a minimum of 4‐year follow‐up. Clinical notes and owner questionnaires identified dogs that subsequently developed lameness and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 17 publications
1
12
0
Order By: Relevance
“…Three hundred and seventeen records were reviewed. Eighty two records were excluded due to concurrent CCL tear (42), no m-TTT performed (17), lack of follow up or incomplete records (9), angular limb deformities requiring distal femoral ostectomy (4), or wrong species (10) Body weight ranged from 1.3 kg to 72.3 kg, with a mean of 14.3 kg. Weight categories 4 included 116 small, 52 medium, 56 large, and 11 giant breeds.…”
Section: Demographicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Three hundred and seventeen records were reviewed. Eighty two records were excluded due to concurrent CCL tear (42), no m-TTT performed (17), lack of follow up or incomplete records (9), angular limb deformities requiring distal femoral ostectomy (4), or wrong species (10) Body weight ranged from 1.3 kg to 72.3 kg, with a mean of 14.3 kg. Weight categories 4 included 116 small, 52 medium, 56 large, and 11 giant breeds.…”
Section: Demographicsmentioning
confidence: 99%
“…Stabilizing the patella reduces pain and lameness, thereby minimizing the worsening of skeletal deformities and osteoarthritis (OA). 2,6,[8][9][10][11] Surgical treatment may require an appropriate combination of techniques to realign the extensor mechanism. 2,10,11 These techniques may include parapatellar soft tissue desmotomy or imbrication, sulcoplasty, antirotational suture, tibial tuberosity transposition (TTT), and femoral corrective ostectomy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study evaluating canine occult grade II MPL showed that the number needed to treat was two (Hamilton et al . 2020). This means that, after a minimum of 4‐year follow‐up, if surgery had been performed in all cases with occult MPL, for every dog in which surgery would have prevented an adverse outcome, another dog would have received an unnecessary surgical procedure.…”
Section: Decision‐making In Treatment Of Mplmentioning
confidence: 99%
“…It has been reported that for every occult grade 2 medially luxating patella that was presented to a clinic and surgically corrected, 1 dog would have had an unnecessary surgery to prevent lameness within 4 years. 6 Reported postoperative complication rates vary between 13% and 48%. 7 A common complication is reluxation, which has been reported in 8% and 48% of operated dogs and is more likely to occur in large breed dogs.…”
mentioning
confidence: 99%